A metal-enhanced fluorescence study of primary amines: determination of aminoglycosides with europium and gold nanoparticles. Issue 4 (12th January 2015) - Caglayan, Mehmet Gokhan; Onur, Feyyaz
Abstract : This paper describes a lipoic acid capped europium nanoparticle-based assay for the fluorimetric detection of primary amines. Abstract : This paper describes a lipoic acid capped europium nanoparticle-based assay for the fluorimetric detection of primary amines. The assay is based on fluorescence quenching resulting from complex formation between amines and lipoic acid on the surface of europium nanoparticles. For the application of the assay, the aminoglycosides were determined in pharmaceuticals and milk. The determination of the aminoglycosides were conducted via fluorescence quenching at 315 nm ( λ ex = 280 nm) at a pH of 5. The metal enhanced fluorescence method with gold nanoparticles was used, in order to enhance the fluorescence of europium nanoparticles. In this manner, the detection limits of aminoglycosides were lowered. The Stern–Volmer constants and the ground-state UV spectra of interaction proved the static quenching that stemmed from the reaction between amines and lipoic acid. Three members of aminoglycosides; amikacin, gentamicin and tobramycin were quantified in the range of 0.75–27.5 μg mL −1, 0.40–26 μg mL −1 and 0.20–25 μg mL −1, respectively.